2003
DOI: 10.1002/xrs.666
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a spectrum fitting procedure using a robust peak model

Abstract: The need for an accurate description of characteristic x-ray lines has led to the development of complex peak models that combine a Gauss, a shelf and a tail function. Via relationships that describe the shelf and tail parameters as a function of the energy, it is possible to reduce the number of fit parameters significantly. In this work, we carried out an experiment to study the shelf and tail parameters obtained with an HPGe detector. We observed a strong discontinuity in the shelf and tail parameters aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…After energy calibration, the fluorescence spectra were analyzed following Ref. [23], using a Gaussian peak for each line with an energy dependent width, a shelf, and a tail accounting for detector related phenomena. The fluorescence of each element was determined by linear fitting, whereas the parameters of the width, tail, and shelf fraction were determined using a nonlinear Levenberg-Marquardt algorithm.…”
mentioning
confidence: 99%
“…After energy calibration, the fluorescence spectra were analyzed following Ref. [23], using a Gaussian peak for each line with an energy dependent width, a shelf, and a tail accounting for detector related phenomena. The fluorescence of each element was determined by linear fitting, whereas the parameters of the width, tail, and shelf fraction were determined using a nonlinear Levenberg-Marquardt algorithm.…”
mentioning
confidence: 99%
“…Our message differs from all previous investigators, as we declare that the signal processor DOES modify the spectra as confirmed by experiments. We recommend the reader look at the spectra presented in the literature [19][20][21][22][24][25][26] to see the large variations.…”
Section: Discussionmentioning
confidence: 99%
“…Since the tail is part of the spectrum it has to be accounted for, and it is a frequent exercise to determine parameter values used to describe these features. One of the latest is the paper of Van Gisel et al 22 They used a digital signal processor and a germanium detector. The spectra have a large amount of tailing reaching up to 100% of the peak area.…”
Section: Quality Control Issuesmentioning
confidence: 99%
“…A wide list of parameters is needed for the definition of the detector, including the sensitive material, surface layers material and thickness, window material and thickness, electron-hole-pair creation energy, Fano factor, electronic noise, and specific parameters for the detector response function). Currently, two different algorithms have been implemented for the detector response function: the fully empirical approach by van Gysel et al [27] and the more physical one by Scholze et al [28] The calculation of pile-up intensities has also been implemented with a strategy following the description of Van Espen. [29] The geometric correction for the fluorescence signal is based on the one proposed by Beckhoff et al, [30] but it has been extended to all possible positioning of the detector on the plane of the beam.…”
Section: Conceptual Scheme Of the Modelling For The Simulation Of A Mmentioning
confidence: 99%